Prospects for Cooperation of Russian and French Multinational Energy Companies on the Basis of National Energy Strategies - M. S. Ovakimyan (Vestnik MGIMO-Universiteta)
The article analyses possible areas of mutually advantageous cooperation of Russian and French multinational energy companies enabling Russia to upgrade its fuel-energy complex and attract adequate investments for large-scale projects realization and France can benefit by participating in new gas mains construction for diversifying its energy supplies and by acquiring shares of Russian multinational energy companies in order to resolve national energy security problem and strengthen its position in the international energy market.